Cultural Structure of Solar Terms and Traditional Festivals - Tao Siyan (Contemporary Social Sciences, 2018)
Solar terms and festivals differ from and relate to each other in terms of application scope and cultural structure.The cultural association and application of the 24 Solar Terms are studied in the areas including philosophy,farming and society,and are exhibited in the natural convergence of views on space and time,life and customs,as well as the facilitation of agricultural practice.The connotations of traditional Chinese festivals concern basic areas such as beliefs,rites,language,symbols,diets and art,which are exhibited in the co-existent "festival tokens," "festival events," "festival messages," "festival symbols," "festival food" and "festival art forms." Festivals feature fixed and periodic occurrence and multi-channel cultural inheritance.